Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.6061/clinics/2015(09)02
|View full text |Cite
|
Sign up to set email alerts
|

Temporal resolution in individuals with neurological disorders

Abstract: OBJECTIVE:Temporal processing refers to the ability of the central auditory nervous system to encode and detect subtle changes in acoustic signals. This study aims to investigate the temporal resolution ability of individuals with mesial temporal sclerosis and to determine the sensitivity and specificity of the gaps-in-noise test in identifying this type of lesion.METHOD:This prospective study investigated differences in temporal resolution between 30 individuals with normal hearing and without neurological le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…At the other end of the temporal scale, while processing of sub-second intervals between sounds draws largely on extra-hippocampal structures, such as cerebellum and striatum ( Nani et al, 2019 , Teki and Griffiths, 2016 ), there is some indirect evidence for hippocampal involvement at these shorter timeframes (see Supplementary Table I). Patients with medial temporal lobe epilepsy including hippocampal sclerosis have problems identifying patterns of durations of hundreds of milliseconds ( Han et al, 2011 ), making anisochrony judgments on the order of tens of milliseconds ( Lavasani et al, 2013 ), and detecting gaps in noise at below 10 ms ( Ehrlé, 2001 , Rabelo et al, 2015 ). Replicating these findings in other groups with circumscribed hippocampal damage will be valuable.…”
Section: Time and Working Memory For Soundmentioning
confidence: 99%
“…At the other end of the temporal scale, while processing of sub-second intervals between sounds draws largely on extra-hippocampal structures, such as cerebellum and striatum ( Nani et al, 2019 , Teki and Griffiths, 2016 ), there is some indirect evidence for hippocampal involvement at these shorter timeframes (see Supplementary Table I). Patients with medial temporal lobe epilepsy including hippocampal sclerosis have problems identifying patterns of durations of hundreds of milliseconds ( Han et al, 2011 ), making anisochrony judgments on the order of tens of milliseconds ( Lavasani et al, 2013 ), and detecting gaps in noise at below 10 ms ( Ehrlé, 2001 , Rabelo et al, 2015 ). Replicating these findings in other groups with circumscribed hippocampal damage will be valuable.…”
Section: Time and Working Memory For Soundmentioning
confidence: 99%
“…The data extraction is shown in Table 4 . Ten papers ( 12 , 22 27 , 30 , 32 , 33 ) were included, but only seven papers that presented GIN results in terms of thresholds (duration of the gap in milliseconds) were further processed in the meta-analysis. The studies by Rabelo, Weihing, and Schochat ( 30 ) reported the results separated by ears.…”
Section: Resultsmentioning
confidence: 99%
“…Ten papers ( 12 , 22 27 , 30 , 32 , 33 ) were included, but only seven papers that presented GIN results in terms of thresholds (duration of the gap in milliseconds) were further processed in the meta-analysis. The studies by Rabelo, Weihing, and Schochat ( 30 ) reported the results separated by ears. Jafari et al ( 25 ), Lavasani et al ( 27 ), and Bamiou et al ( 23 ) reported the GIN results separated by ears and sides of lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Although this procedure might have compromised the p-values calculated in the present study due to a possible violation of the assumption of independence of observations, it may be an interesting move in order to reduce the number of measures to be analyzed in clinical practice and to increase statistical power of the sample. It is also worth noting that grouping the ears together is a data analysis procedure used in other studies in the audiology field (e.g., [ 60 , 61 , 62 , 63 , 64 ]). Another limitation might be the predominance of female subjects in our sample, although previous research found no difference between genders regarding BMT performance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%